Assessment of nutrient limitation in fertilized fish ponds by algal assay - Guttman, Hans; Knud-Hansen, Christopher F.; Edwards, Peter; Lin, Chang Kwei (Bangkok : Asian Institute of Technology, 1991)
A provisional technique for field (outdoor) algal assay procedure was devised; using either a 125 mL Erlenmeyer flask or a 70 mL test-tube as an incubation vessel with a 25 to 30 mL sample covered with a loose fitting aluminum cap, incubating under a shade cloth for 3-4 days at ambient air temperatures and shaking the vessel s three times daily. An algal assay methodology for determining the limiting nutrient (carbon, nitrogen or phosphorus) for fertilized fishponds using the above technique and indigenous algal cultures was devised and tested. Results indicated full agreement between assay results and nutrient limitation for prepared algal growth media. Tests of pond waters showed a good agreement between assay responses and nutrient ratios of the waters tested. Visual assessment of assay responses were evaluated and found that over 90% of people involved (n= 15) could separate a chlorophyll a difference of < 10 mg/m3 for a 100 mL sample filtered on to a Whatman GF/C filter. Algal yield dose response patterns to phosphorus spiking of phosphorus limited cultures followed a asymptotic relation (r2 > 0.86, p < 0.001 for six trials). Analysis of the regression slopes showed a significant correlation (r2 = 0.85, p < 0.01) between the s lopes and the initial dissolved inorganic nitrogen (DIN) of the culture media. This lends support to the underlying theories for assessment of DIN through a l gal assays. Dose response experiments showed a significant and relatively close correlation (r = 0.68, p< 0.001) between initial DIN and visually assessed spike saturation levels (the amount of spike needed to make DIN limiting) for phosphorus limited algal cultures. Investigations by algal assay of pond/tank waters used for fish culture at the Asian Institute of Technology, Bangkok, showed a dominance of nitrogen limitation (six out of nine cases). From these results a pattern of increased algal yield (measured as % over control) was determined as C:N ratio increases and N:P ratio decreases.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Fish ponds